REFLECTIONS ON THE TEACHING & LEARNING ONLINE APPROACH: A CONTEMPORARY CHALLENGE? OR A THREAT? - Kapareliotis Ilias; Crosbie Patricia (European Scientific Journal, ESJ, 2014)
An academic starting work in a new environment is challenging. In addition recent technological developments and advancements mean we are all having to change our lifestyles, our habits and even our behaviour. Behaviourism where different behaviours are adopted according to the circumstances is the approach I try to adopt in my teaching which is mainly on postgraduate courses. I adopt the same approach for my everyday life. However, it is hard to say identify what types of behaviour I will develop as technological advancement influence my behaviour in both my personal and professional life. What I do know is that my behaviour will have to change and I recognise a need for equilibrium between my online and offline personality.